A new approach to visualizing general trees using thickness-adjustable quadratic curves - Rostami, M. Ali; Azadi, Azin; Bücker, H. Martin (GD'14: Proceedings of the International Symposium on Graph Drawing, 2014)
We present a new algorithm for visualization of trees. This algorithm illustrates the hierarchical data by using curve segments for each edge and how edges evolve on a path from the root to the leaves. More clearly, we visualize a tree based on the shape of a botanical tree. The software tool GraphTea implements this algorithm where the adjustable thicknesses of the curve segments reflect the expansion of botanical trees. Here, we consider a simple expansion definition for each vertex as the sum over the number of children and the children of its children up to the some specific level.